Respuesta :

Answer:

5. (2x-5)/(3x^2-10x+3)

6. 3/(4x+4)

Step-by-step explanation:

There is nothing to "solve." The expressions can be simplified.

5.

[tex]\displaystyle\frac{\left(\frac{2x-5}{x^2-9}\right)}{\left(\frac{3x-1}{x+3}\right)}=\frac{2x-5}{x^2-9}\cdot\frac{x+3}{3x-1}=\frac{(2x-5)(x+3)}{(x+3)(x-3)(3x-1)}\\\\=\frac{2x-5}{(x-3)(3x-1)}=\frac{2x-5}{3x^2-10x+3}[/tex]

__

6.

[tex]\displaystyle\frac{\frac{x}{x+1}}{x+\frac{x}{3}}=\frac{x}{x+1}\cdot\frac{3}{3x+x}=\frac{3x}{4x(x+1)}\\\\=\frac{3}{4x+4}[/tex]

ACCESS MORE